The factors influence on consumers purchase intention and purchase decisions of organic food in Indonesia - Septiani, Jerni Sari; Hakim, Dani Lukman; Rahmiati, Filda; Amin, Grace; Mangkurat, R. Stevanus Bayu (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Organic products in Indonesia represent 0.03% of global demand. Health problems are one of the causes of increasing consumer awareness in the world to maintain health and reduce environmental impact. The organic market is growing, but obstacles awareness still prevents it. The purpose of this research is to examine the influence of health consciousness, perceived quality, and environmental awareness of organic food in Indonesia. Methods: A quantitative method was used and the data acquired through Google form. The research design method by conducting online questionnaires. The questionnaires were distributed online for those who intend to purchase organic food in Indonesia. The total respondents in this research are 180. The data analysis design used in this research is Partial Least Square-based Structural Equation Modeling (PLS-SEM) using Smart-PLS, starting from the measurement of outer model, inner model, and hypothesis testing. Result: This study has 7 hypotheses and the results showed that health consciousness, perceived quality, directly influencing purchase decision and indirectly mediated by purchase intention. Conclusion: However, environmental awareness has no direct and indirect influence on consumer purchase decisions of organic food in Indonesia. Novelty/Originality of this study: Using the PLS-SEM method, this study provides in-depth insights into how these factors influence purchase intention, while environmental awareness does not show a significant influence.